What Strategies are Employed in the Implementation of Sharia Bank Green Banking? - Syarvina, Wahyu; Tarigan, Azhari Akmal; Marliyah, Marliyah (EQUILIBRIUM, 2023)
Green banking is an approach that aims to mitigate market competition and preserve the environment since the banking sector is reliant on a healthy environment for its sustainability. If the banking sector does not implement this, it will increase legal risks, financing risks, and the bank's reputation. This research aims to find out the green banking development strategy of Sharia banks in Indonesia, along with the problems and potential solutions for its implementation. This research employs the Analytic Network Process (ANP) method and is processed using the SuperDecision software. The findings of this study reveal that Islamic banking in Indonesia has three distinct problems: The primary focus is on regulatory issues, followed by human resources problems, and subsequently, governance matters. Respondents have a rater agreement of W = 0.10345. The best solution to overcome the problem of developing green banking for Islamic banks in Indonesia is a human resources solution, followed by a regulatory solution and a governance solution. The level of respondent agreement or rater agreement W = 0.05461. Strategies for developing green banking for Sharia banks in Indonesia include improving the quality of human resources, implementing government support initiatives, and strengthening governance systems. Respondents have a rater agreement of W = 0.04598. Strategies for developing green banking for Sharia banks in Indonesia include strategies for improving the quality of human resources through employee green training and capabilities, strategies for implementing government support initiatives through the establishment of policies that facilitate the enactment of green banking in Sharia banks, and strategies for strengthening governance system by complying with the precautionary principle for an excellent image of Sharia banks.